1992
DOI: 10.1093/infdis/166.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Human T Cell Lymphotropic Virus Type II Infection among Isolated Brazilian Amerindians

Abstract: Evidence for human T cell lymphotropic viruses (HTLV) was sought in sera and cells collected from adults in 13 isolated South and Central American Indian tribes. Serologic tests identified frequent HTLV-II-like reactivity among the Cayapo and Kraho tribes, who live 330 km apart in Central Brazil. Polymerase chain reaction analyses of viral DNA in cell pellet and plasma fractions confirmed the virus as HTLV-II. Both tribes speak Gé and, at the time of blood collection (1974), subsisted as hunter/gatherers and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
4

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(98 citation statements)
references
References 26 publications
2
92
0
4
Order By: Relevance
“…The DNA was extracted using phenol-chloroform (Life Technologies), precipitated with ethanol and dissolved in Milli-Q water (Millipore). DNA from 105 cells was used for amplification with the nested TR101-104 primer set (tax region; Maloney et al, 1992) or with the nested PCR primer set TR101-HFL102 (outer)/TR103-HFL104 (inner) [HFL102, 5' TG(A/T)A(G/C)TAC(C/T)AAAGATGGCTG 3' (antisense, complementary to nt 8115 8134 of HTLV-I ATK1); HFL104, 5' GG(C/T)A(A/G)GGICCGGAAATCAT 3' (antisense, complementary to nt 8085 8103 of ATK1)]. All amplifications were done in PCR buffer, 200 lara nucleotide triphosphates, 0.8 laM outer primers or 0.5 IxM inner primers and 0.025 U/~tl AmpliTaq (Perkin-Elmer) using 3 mraMgCla for the TR primers and 2 mM-MgCI 2 for the TR/HFL primer sets, in a 50 ~tl reaction volume.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA was extracted using phenol-chloroform (Life Technologies), precipitated with ethanol and dissolved in Milli-Q water (Millipore). DNA from 105 cells was used for amplification with the nested TR101-104 primer set (tax region; Maloney et al, 1992) or with the nested PCR primer set TR101-HFL102 (outer)/TR103-HFL104 (inner) [HFL102, 5' TG(A/T)A(G/C)TAC(C/T)AAAGATGGCTG 3' (antisense, complementary to nt 8115 8134 of HTLV-I ATK1); HFL104, 5' GG(C/T)A(A/G)GGICCGGAAATCAT 3' (antisense, complementary to nt 8085 8103 of ATK1)]. All amplifications were done in PCR buffer, 200 lara nucleotide triphosphates, 0.8 laM outer primers or 0.5 IxM inner primers and 0.025 U/~tl AmpliTaq (Perkin-Elmer) using 3 mraMgCla for the TR primers and 2 mM-MgCI 2 for the TR/HFL primer sets, in a 50 ~tl reaction volume.…”
Section: Methodsmentioning
confidence: 99%
“…From both the original lymphocytes and the PP1664 cell line, a 159 bp fragment was obtained in a nested PCR using the TR101-104 primers (Liu et al, 1994b;Maloney et al, 1992). The SK110-111 primers (Kwok et al, 1988) in the pol region gave negative results (data not shown).…”
Section: Amplification and Sequencing Of A Tax~rex Fragment From The mentioning
confidence: 97%
See 1 more Smart Citation
“…4 More interestingly, HTLV-1 and HTLV-2 have been identified in several aboriginal Indian populations in the Americas. 4,5 New World Indian tribes in which an elevated prevalence of HTLV-2 has been reported include the Guaymi tribe of Panama, 6 the Athapaskan and Pueblo groups of the southwestern United states, 7 the Ge-speaking tribes of Amazonia, 8 Florida Indians, 9 the Wayuu 10 and Tunebo Indians of Colombia, 11 and the Tobas of Bolivia and Paraguay. 12 Recently, a high rate of infection with HTLV-2 has been reported in Indian populations from Argentina.…”
mentioning
confidence: 99%
“…From the blood sample of OU-KA DNA was isolated and analysed in a semi-nested PCR assay specific for the tax\rex region of HTLV-I\STLV-I and HTLV-II (Maloney et al, 1992 ;Ibrahim et al, 1995). A 118 bp fragment was amplified indicating infection of OU-KA with a HTLV-like virus (results not shown).…”
mentioning
confidence: 99%